Fetal Gastroschisis: A Comparison of Second vs. Third-Trimester Bowel Dilatation for Predicting Bowel Atresia and Neonatal Outcomes - Lato, K.; Qweider, M.; Poellmann, M.; Knippel, A. J.; Bizjak, G.; Stressig, R.; Hammer, R.; Janni, W.; Kozlowski, P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To compare various gestational ages and thresholds for diagnosing bowel dilatation in fetuses with gastroschisis and to evaluate the prognostic value of bowel dilatation for predicting postnatal bowel atresia and neonatal outcomes.Materials and Methods: This was a retrospective observational study conducted from March 1997 to September 2009 that included 78 pregnancies with fetal gastroschisis. The predictive value of prenatal bowel dilatation for neonatal bowel atresia and postnatal complications was investigated in three subgroups: those with bowel dilatations ≥ 10 mm at a gestational age < 27 + 0 weeks, ≥ 10 mm at a gestational age < 30 + 0 weeks and ≥ 18 mm at a gestational age ≥ 30 weeks.Results: Prenatally, 6 %, 81 % and 13 % of the bowel malformations were identified in the first, second and third trimesters, respectively. There were three stillbirths and three neonatal deaths, and the mean gestational age at delivery was 35.4 weeks (range 31 + 4 to 41 + 6). Bowel atresia was significantly correlated with prenatal bowel dilatation in all three subgroups. Bowel dilatations of ≥ 10 mm before 30 + 0 gestational weeks achieved the best performance in predicting bowel atresia, with a sensitivity of 89 % (8 / 9) and a specificity of 79 % (30 / 38). A prenatal bowel diameter ≥ 10 mm through 30 completed weeks was also the best predictor of a prolonged neonatal hospital stay ≥ 8 weeks (sensitivity = 61.1, 11 / 18, p = 0.002).Conclusion: Fetuses with isolated gastroschisis successfully underwent postnatal surgery in most cases (93.2 %), except for one termination, one intrauterine death and 3 cases of neonatal death. A fetal bowel dilatation > 10 mm before 30 + 0 weeks had the highest predictive value for postnatal bowel complications.
Keywords: abdominal wall; ultrasound 2 D; malformation; bowel atresia; bowel dilatation